Dedicated spectral method of Boolean function decomposition - Porwik, Piotr; Stanković, Radomir S. (Zielona Góra: Uniwersytet Zielonogórski)
Spectral methods constitute a useful tool in the analysis and synthesis of Boolean functions, especially in cases when other methods reduce to brute-force search procedures. There is renewed interest in the application of spectral methods in this area, which extends also to the closely connected concept of the autocorrelation function, for which spectral methods provide fast calculation algorithms.
Keywords: Boolean function; Walsh spectrum; autocorrelation coefficients; disjoint decomposition